Assessing Facial Thermal Nociceptive Response in Female Dogs After Elective Ovariohysterectomy Anesthetized with Isoflurane and Treated with Cannabidiol and Meloxicam Analgesia - Alejandro Casas-Alvarado; Patricia Mora-Medina; Ismael Hernández-Avalos; Julio Martínez-Burnes; Agatha Miranda-Cortes; Adriana Domínguez-Oliva; Daniel Mota-Rojas (Animals)
Pain management requires the identification of certain indicators to recognize pain. Various tools have been suggested to achieve an objective evaluation, including infrared thermography (IRT). The objective of this study was to assess the facial thermal nociceptive response produced by the use of cannabidiol (CBD) alone and in combination with meloxicam in female dogs undergoing elective ovariohysterectomy anesthetized with isoflurane. Sixty-four female dogs of different breeds were randomly distributed into four study groups according to the treatment received. G1: Placebo group (n = 16); G2: Group receiving intravenous meloxicam as premedication (0.2 mg Kg−1) and every 24 h postoperatively 0.1 mg Kg−1 (n = 16); G3: Group treated with CBD (n = 16) at a dose of 2 mg kg−1 orally every 12 h; and G4: Group medicated with the combination of both treatments (n = 16). All treatments were administered for 48 h postoperatively. After the anesthetic surgical procedure, radiometric images were captured using IRT and physiological parameters during the events EBasal, E30min, E1h, E2h, E3h, E4h, E8h, E12h, E24h and E48h. Overall, it was found that the high, medium and low temperatures of the thermal windows of the eye, upper eyelid and lower eyelid, as well as the average temperature of the lacrimal gland in G1 between events, were significantly lower at E30min, E1h and E2h compared to EBasal (p = 0.01). Among treatments, a significantly higher temperature was observed in groups G2, G3 and G4 compared to G1 (p = 0.001) in the thermal windows of the upper eyelid, lower eyelid, lacrimal gland and ocular areas. Regarding physiological parameters, heart rate (HR) was higher in G1 compared to the animals in G2, G3 and G4 (p = 0.03). The respiratory rate (RR) was significantly lower in all four study groups during the postoperative events compared to their respective EBasal (p < 0.05), while among treatments, G2, G3 and G4 had a lower RR compared to G1 (p = 0.03). Mild hypothermia was observed in all study groups at E30min and E1h compared to EBasal (p = 0.001). No significant correlation was found between the temperatures of the assessed thermal regions and the physiological traits. In conclusion, CBD, whether administered alone or in combination with meloxicam, demonstrated comparable analgesic efficacy, which could control nociceptive cardiorespiratory and hemodynamic autonomic responses, as there were no significant changes in the facial thermal response between treatments G2, G3 and G4.